Amphotericin B, the Wonder of Today's Pharmacology Science: Persisting Usage for More Than Seven Decades - Falah Hasan Obayes al-Khikani (Mazandaran University of Medical Sciences, 2020)
Background: Despite several available topical and systemic antifungal drugs for the treatment of fungal infections, Amphotericin B (AmB) is still one of the most common first-line choices in treating systemic fungal infection for more than seven decades after its discovery. Objectives: Amphotericin B which belongs to the polyene group has a wide spectrum of in vitro and in vivo antifungal activity. Its mechanism of antifungal action is characterized by creating a pore in the fungal plasma membrane leading to cell death. Methods: In addition to the old formula of deoxycholate-Amphotericin B (D-AmB), three lipid formulas have been developed to reduce the adverse effects of conventional AmB (D-AmB) in the human body and increase its therapeutic efficacy. All of the known available formulas of AmB are administrated via intravenous injection to treat severe systemic fungal infections, while the development of the topical formula of AmB is still under preliminary research. Numerous pharmaceutical formulas of systemic and topical applications with clinical uses of AmB in just humans, not in vitro or animals model, against various fungal infections are discussed in this review. Topical AmB formulas are a promising way to develop effective management and to reduce the adverse effects of intravenous formulas of AmB without laboratory monitoring. Results: The wonderful pharmacological properties of AmB with its prolonged use for about seven decades may help researchers to apply its unique features on other various antimicrobial agents by more understanding about the AmB mechanisms of actions. Conclusion: Amphotericin B is widely used intravenously for the treatment of systemic fungal infection, while the topical formula of AmB is still under experimental study.